Comprehensive Ruby programming go from beginner to confident programmer - Hudgens, Jordan (Packt Publishing, 2017)
This book will provide you with all of the tools you need to be a professional Ruby developer. Starting with the core principles, such as syntax and best practices, and up to advanced topics like metaprogramming and big data analysis. About This Book Provides the core skills required to become a Ruby programmer Covers how to use the most popular Ruby Gem libraries Includes details on regular expressions Who This Book Is For This is a complete course written from the ground up for beginners wanting to gain a solid understanding of the Ruby language. It starts at the beginning with how to install Ruby and work with it on multiple machines, so simply have a computer that's connected to the Internet and you'll be ready. What You Will Learn Learn how to use Ruby code effectively, picking the right tool for the job and not duplicating built-in functionality Gain best software development practices, and how to identify and fix common errors Absorb core programming skills, such as variables, strings, loops, conditionals, and much more Explore object-oriented programming and learn to create modular, reusable code that you can use across projects Build 10 practical Ruby programs as you work through the book on topics such as big data analysis and solving Euler equations In Detail Ruby is a powerful, general-purpose programming language that can be applied to any task. Whether you are an experienced developer who wants to learn a new language or you are new to programming, this book is your comprehensive Ruby coding guide. Starting with the foundational principles, such as syntax, and scaling up to advanced topics such as big data analysis, this book will give you all of the tools you need to be a professional Ruby developer. A few of the key topics are: object-oriented programming, built-in Ruby methods, core programming skills, and an introduction to the Ruby on Rails and Sinatra web frameworks. You will also build 10 practical Ruby programs. Created by an experienced Ruby developer, this book has been written to ensure it focuses on the skills you will need to be a professional Ruby developer. After you have read this book, you will be ready to start building real-world Ruby projects. Style and approach This is a comprehensive course for learning the Ruby programming language that works methodically through everything that you need to know. It begins with the basics of the language and then works through some complete projects to apply your skills and...
Description based on online resource; title from title page (Safari, viewed July 24, 2017)
Keywords: Ruby (Computer program language); Ruby (Langage de programmation); COMPUTERS / Programming Languages / Ruby